Edukasi Pentingnya Literasi dan Pengarahan Penggunaan Gadget Pada Sekolah Master Indonesia-Depok - Azzahra, Najwa; Maryam, Clarissa Amalia; Wijaya, Natalie; S, Subakdi; Lewoleba, Kayus Kayowuan; S, Suprima; Manalu, Ronald; Priyono, Edi; Bramantyo, Rm Andreas (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This activity addresses the themes of literacy and guidance on gadget use, aiming to equip children at Sekolah Master Depok with the skills needed to navigate modern life while maintaining positive activities like reading. In an increasingly sophisticated digital world, gadgets are not something foreign across all age groups, including children. While these technologies provide easy access to both beneficial and harmful content, the need for digital literacy has never been more urgent. UNESCO reports that Indonesia’s reading interest index is just 0.001%, meaning only one in every 1,000 Indonesians is an avid reader. Furthermore, Senior Economist Aviliani of INDEF highlights that Indonesia's digital literacy rate is only 62%, the lowest in ASEAN, where the average is around 70%. In response to these concerns, this activity was implemented at schools that cater to children with limited access to educational resources. Several strategies were employed, including explaining the positive impacts of literacy, introducing books and educational apps, discussing the negative consequences of excessive gadget use, and guiding students on how to use gadgets for productive purposes. The final results (outputs) produced from the activity that will be achieved are in the form of articles, videos, and posters designed to encourage positive behaviors. The expected benefits include a greater interest in literacy and the responsible use of gadgets, particularly for children in underprivileged areas. Additionally, the program aims to prevent the negative effects of digital devices, such as exposure to pornography and online gambling.